Analisis Faktor-faktor yang Memengaruhi Minat Sertifikasi Halal pada Pelaku UMKM di Jawa Timur - Larasati, Anita; Yasin, Ach (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The large percentage of the Muslim population in Indonesia is a great opportunity to become the largest producer of halal products and services in the world. Since the enactment of Law No. 33 of 2014 concerning Guaranteed Halal Products, halal certificates are mandatory for products imported, distributed and traded in Indonesia. One sector that is prone to product halal issues is MSME. This study aims to analyze the factors that influence interest in halal certification in MSME actors in East Java. This study uses the variables understanding halal certification, halal awareness, and halal certification costs. Using quantitative methods with multiple linear regression analysis. The analytical tool used was SPSS version 25. The data used in this study were primary data obtained by distributing questionnaires in the form of a Google form. Sampling used a purposive sampling technique with sample criteria namely food and beverage MSME actors who are domiciled in East Java, especially Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan, and have been running a business for 2 years or more. The results of the study show that partially the understanding of halal certification and halal awareness has an effect on the interest in halal certification among MSME actors in East Java. When the understanding of halal certification and halal awareness increases, the interest in halal certification for business actors also increases. Partially, the cost of halal certification has no effect on interest in halal certification in MSME actors in East Java